The transparent self - Jourard, Sidney M. (Van Nostrand Reinhold Company, 1971)
Throughout history, the author maintains, man has chosen the road of concealment rather than "openness", a route that all too often results in sickness, misunderstanding and alienation from self. The author explores the implications of a new premise: man can attain health and fullest personal development only insofar as he gains courage to be himself with others and only when he finds goals that have meaning for him, goals which include the reshaping of society so that it is fit for all to live and grow in.